SOCIO-EMOTIONAL CONDITIONS OF MOTHERS AND BEHAVIORAL PROBLEMS OF CHILDREN IN PRESCHOOL IN VILLA MARIA DEL TRIUNFO – LIMA, PERU - Iannacone-Alvariño, Dafne Lorelei (2022)
The study proposes to determine the relationship between the socio-emotional conditions of the mothers and the behavioral problems of preschool children; considering gender and type of educational management. The sample consisted of 154 mothers and their preschool children between the ages of three and five from two schools, one private and one state, in the district of Villa María del Triunfo, Lima, Peru. The Inventory of Behavioral and Socioemotional Problems (IPCS) adapted in Metropolitan Lima by Cossio-2014 was used. The design is descriptive-comparative and correlational, and seeks to compare the results according to gender and type of educational management and to correlate the study variables, socio-emotional conditions and behavioral problems. According to the results, it can be affirmed that the socio-emotional conditions of the mothers are positively related to the behavioral problems of the children. A relationship was found between depressive mood of the mothers and the categories aggressiveness, withdrawal, anxiety and diminished image of the children. A correlation was also found between the couple's relationship and the categories aggressiveness, withdrawal and anxiety. In the isolation category, there is a relationship with the aggressiveness, anxiety, diminished image and fear categories. Family problems are related to the categories aggressiveness, strange behavior, anxiety, diminished image and gender behavior. Boys are more immature than girls. In addition, in the comparison according to the type of educational management, it is found that there are more socio-emotional conditions in the mothers and behavioral problems in the private school. Key words: behavioral problems – couple's relationship –Family problems –  mothers and children – Socio-emotional conditions